Revisiting the Effect of Pharmaceuticals on Transmission Stage Formation in the Malaria Parasite Plasmodium falciparum - Thommen, Basil T.; Passecker, Armin; Buser, Tamara; Hitz, Eva; Voss, Till S.; Brancucci, Nicolas M. B. (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria parasites rely on specialized stages, called gametocytes, to ensure human-to-human transmission. The formation of these sexual precursor cells is initiated by commitment of blood stage parasites to the sexual differentiation pathway. Plasmodium falciparum, the most virulent of six parasite species infecting humans, employs nutrient sensing to control the rate at which sexual commitment is initiated, and the presence of stress-inducing factors, including antimalarial drugs, has been linked to increased gametocyte production in vitro and in vivo. These observations suggest that therapeutic interventions may promote gametocytogenesis and malaria transmission. Here, we engineered a P. falciparum reporter line to quantify sexual commitment rates after exposure to antimalarials and other pharmaceuticals commonly prescribed in malaria-endemic regions. Our data reveal that some of the tested drugs indeed have the capacity to elevate sexual commitment rates in vitro. Importantly, however, these effects are only observed at drug concentrations that inhibit parasite survival and only rarely result in a net increase of gametocyte production. Using a drug-resistant parasite reporter line, we further show that the gametocytogenesis-promoting effect of drugs is linked to general stress responses rather than to compound-specific activities. Altogether, we did not observe evidence for mechanistic links between the regulation of sexual commitment and the activity of commonly used pharmaceuticals in vitro. Our data hence does not support scenarios in which currently applied therapeutic interventions would promote the spread of drug-resistant parasites or malaria transmission in general.